Golden opportunity for UMPSA Students: Mohamed Noah Foundation commits to RM400,000 Scholarship - Nor Azlina, Ahmad (UMPSA, 2024)
PEKAN, 5 July 2024 – The Mohamed Noah Foundation has reaffirmed its commitment to national education by donating a bursary amounting to RM400,000 to students of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).